2018
DOI: 10.1007/s00429-018-1772-4
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin 8 regulates proliferation of cortical interneuron progenitors

Abstract: Cortical interneurons are born in the ventral forebrain and migrate tangentially in two streams at the levels of the intermediate zone (IZ) and the pre-plate/marginal zone to the developing cortex where they switch to radial migration before settling in their final positions in the cortical plate. In a previous attempt to identify the molecules that regulate stream specification, we performed transcriptomic analysis of GFP-labelled interneurons taken from the two migratory streams during corticogenesis. A numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…6C). Western blots of regional dissections taken from littermates show near complete loss of Cdh8 in PFC (the remainder is consistent with low levels of Cdh8 reported in inhibitory neurons 27 ), but unchanged Cdh8 expression levels in striatum as expected (Fig. 6D).…”
Section: Resultssupporting
confidence: 87%
“…6C). Western blots of regional dissections taken from littermates show near complete loss of Cdh8 in PFC (the remainder is consistent with low levels of Cdh8 reported in inhibitory neurons 27 ), but unchanged Cdh8 expression levels in striatum as expected (Fig. 6D).…”
Section: Resultssupporting
confidence: 87%
“…Interestingly, some of these alterations, including the reduced expression of proteins involved in cell adhesion such as Cdh8 and Neo1, could be related with the expansion in neurogenesis that we observed during development. Indeed, Cdh8 is expressed in the germinal zone during development, and its knockdown amplifies both proliferation and neuron numbers 57 . Similarly, genetic ablation of Neo1 also increases proliferation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Newly postmitotic cells that will become cortical interneurons express the LIM homeobox gene Lhx6 and cadherin-8 (Cdh8) already within the subpallial medial ganglionic eminence. Mice lacking Cdh8 displayed a significant increase in the number of cortical interneurons and in vitro studies confirmed that knockdown of Cdh8 induced proliferation of neural progenitors, whereas over expression of Cdh8 resulted in decreased proliferation (Memi et al, 2019). Interneuron progenitors also express the neuropilin receptors Nrp1 and Nrp2 which mediate their response to semaphorin (Sema) 3 ligands.…”
Section: Neurogenesis In the Mammalian Neocortexmentioning
confidence: 94%